LOOKING FOR REMEDY AND LEARNING ENGAGEMENT OF ENTREPRENEURIAL - Sri Widodo; Budi Santoso (Universitas Katolik Widya Karya Malang, 2023)
Entrepreneurial education (EE) is a process facilitating individuals to recognize, to assess, and to execute business opportunity. Besides, it is also developed as a process to enhance awareness on opportunity recognition, knowledge, self-esteem, and capability to act in various contexts (Morris, Webb, Fu & Singhal, 2013, Jones dan Engish (2004). Entrepreneurial Education has become something beyond business, but also as means or methods to build entreprenurial competences which are also impactful towards the betterment of adaptibility and competitiveness (Allan Gibb, 2002; Mwasalwiba, 2010).